Force and time symmetry analysis for swing to strength hold elements on still rings in men`s artistic gymnastics - Naundorf, F.; Merz, C.; Aarts, M. (dvs-Biomechanik 2023 Tagungsband, 2023)
Still rings routines in men´s artistic gymnastics consist of swing and strength elements without longitudinal rotation. Swings with half turns and crossing of the cables, as performed before 2000, are currently not allowed. Only the dismount can include longitudinal rotations, which occurs during the flight phase. On this basis, the acting forces during the routines are ideally symmetric or almost symmetric. Only in the case of corrections can the forces on the rings differ slightly. This assumption is supported by Carrara et al. (2015), who discovered no significant asymmetry in the element cross using kinematic methods. Swing to Strength hold elements is a requirement of the rules and important for a successful still rings routine in gymnastics. The use of force measurement systems in rings routines can support judges (Aarts et al., 2016), provide a deeper insight into the required strength (Merz et al., 2023) and can produce feedback to gymnasts in training (Lehmann et al., 2021). All systems measure the forces on the left and the right ring independently and sum them afterwards to calculate the total force. Based on the before described assumption of symmetry the aim of this study was to analyse if a doubled single force of one ring produces a good estimate of the total force when compared to the summed forces exerted on left and right.